Efektivitas Pembelajaran Kelas Digital pada Mata Pelajaran Teknlogi Informasi dan Komunikasi Kelas VII SMP Negeri Payakumbuh - Amalia, Zikra; Yusri, Meldi Ade Kurnia; Syafril, Syafril; Rahmayanti, Elsa (Indo-MathEdu Intellectuals Journal, 2024)
Digital classes students follow learning by listening to the teacher's briefing that enters the class, using various needs for learning such as LKS, textbooks, and other media. This study aims to determine the effectiveness of digital classroom learning in the subject of Information and Communication Technology in grade VII of SMP Negeri Payakumbuh. The type of research is quantitative research with a sample of 38 where in this quantitative research uses many numbers. The research method used is a quasi experiment. Data collection is carried out through tests, and data analysis is carried out using t-tests. The results of the study showed that the average score obtained in ICT subjects using google classroom on student learning outcomes was higher than the average score in the control class that used paper sheets. Thus, the t-count is smaller than the t-table, which can be interpreted that there is a significant effectiveness on student learning outcomes between classes that use google classroom in digital classrooms.